Impact of Osmotic Distillation on the Sensory Properties and Quality of Low Alcohol Beer - Liguori Loredana; De Francesco Giovanni; Albanese Donatella; Mincione Antonio; Perretti Giuseppe; Di Matteo Marisa; Russo Paola (Journal of Food Quality)
The production of low alcohol beer (LAB) with a full and well-balanced flavour is still now a complex challenge because of the different flavour profile they have compared to regular beers. In this study, a brown ale beer was used to obtain a low alcohol beer by osmotic distillation in a small pilot plant. Beer-diluted carbonated solutions were used as strippers and were taken under flux of CO2 in order to contrast loss of volatiles from beer during the process. A forced carbonation was applied on LAB to avoid the foam collapse. Furthermore, hop extract and pectin solution were added to LAB to improve the overall taste and body. Results highlighted an improvement into retention of volatiles probably due to the use of carbonated solutions such as strippers. The forced carbonation and the addition of pectins ensured both a higher concentration of dissolved CO2 and a higher stability of foam in LAB. The antioxidant activity of beer remained unchanged. The sensory analysis highlighted differences among low alcohol beer and original one. The addition of hop extract and pectin solution to LAB better maintained hop and fruity-citrus notes during tasting, compared with the original beer.